2022
DOI: 10.3934/agrfood.2022032
|View full text |Cite
|
Sign up to set email alerts
|

Salinity tolerance selection of doubled-haploid rice lines based on selection index and factor analysis

Abstract: <abstract> <p>The development of tolerant rice varieties using doubled-haploid technology is necessary to speed up the release of a variety tolerant to salinity stress. However, this requires a reliable screening method and selection index model for enhancing selection effectiveness. One approach is through the development of a selection index based on factor analysis under soil salinity screening in the greenhouse. The objective of this study was to develop a selection index model based on fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 29 publications
2
21
0
2
Order By: Relevance
“…The interaction between genotype and control can indicate the instability of the appearance of a cultivar in various environments (Dhillion et al, 2009;Dev et al, 2009). In general, significant variance is the initial basis for determining the effectiveness of a character selection character (Sabouri et al, 2008;Anshori et al, 2022;Litrico and Violle, 2015;Priyanto et al, 2018). Therefore, the source of diversity is an essential requirement for line selection in augmented design.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The interaction between genotype and control can indicate the instability of the appearance of a cultivar in various environments (Dhillion et al, 2009;Dev et al, 2009). In general, significant variance is the initial basis for determining the effectiveness of a character selection character (Sabouri et al, 2008;Anshori et al, 2022;Litrico and Violle, 2015;Priyanto et al, 2018). Therefore, the source of diversity is an essential requirement for line selection in augmented design.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the use of path analysis can determine causal relationships and sort out the direct and indirect effects (Li, 1956;Singh and Chaudary, 2010;Kumar et al, 2014;Anshori et al, 2021;Gani et al, 1995), as well as, calculate the characters that contributed significantly to the increase in yield (Abdulkhaleq and Tawfiq, 2014). Still, the direct use of path analysis on many characters becomes inefficient, and it needs filtering with a significant correlation analysis on yield as the main character (Anshori et al, 2021(Anshori et al, , 2022. Both analyses showed that character, total fruit number, diameter, and weight directly influence yield.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations